FAKTOR RISIKO TERKAIT PERDARAHAN VARISES ESOFAGUS BERULANG PADA PENDERITA SIROSIS HATI - Vidyani, Amie; Vianto, Denny; W, Budi; Kholili, Ulfa; Maimunah, Ummi; Sugihartono, Titong; Purbayu, Herry; Boedi Setiawan, Poernomo; A Nusi, Iswan; Adi, Pangestu (journal of internal medicine, 2011)
Recurrent esophageal varices bleeding in liver cirrhosis increase the morbidity and mortality. 50 ! 60% patients with Esophageal Varricess (EV) will experience recurrent bleeding, 30% or one third of them will experience recurrent bleeding one year after diagnosis of EV. Mostly recurrent bleeding will be found at 6 weeks until 6 months after the Þ rst bleeding. Prevention of recurrent bleeding is important for survival. The aim of this research to know the risk factors of recurrent EV bleeding in liver cirrhotic patients and the onset of recurrent bleeding after the Þ rst endoscopy. This is a cross sectional study. Thirty Þ ve decompensated liver cirrhosis patients that fulÞ ll the inclusion and exclusion criteria participated in this study. After the Þ rst endoscopy, the risk factors are written, consist of sex, age, ascites, degree of varices, history of LVE/STE the severity of liver disease, and history of consuming gastric iritating drugs. The patients followed for six months to evaluated the occurence of recurrent bleeding. We used Pearson Chi-Square test for statistic analysis (signiÞ cant if p < 0.05). SPSS 17 were used to statistic calculation. Statistic analytical showed signiÞ cant correlation (p = 0.006; OR = 8.889; CI: 1.803 ! 43.820). On the other hand sex, age, degree of EV, history of STE/LVE showed non signiÞ cant correlation. The main risk factor of recurrent EV in liver cirrhosis is the severity of liver disease.